Postinfarction ventricular septal rupture - a rare complication remains challenge for cardiac surgical team - Rohn, V; Grus, T; Lindner, J; Lipš, M; Bělohlávek, J (Prague medical report, 2013)
The incidence of post infarction ventricular septal rupture (PIVSR) is decreasing in the last years due to aggressive treatment of myocardial infarction with early percutaneous coronary interventions. As a consequence patients with PIVSR are referred to surgery more often with significant heart failure. The aim of this retrospective study was to assess the influence of these on the operative results and to identify the risk factors of operative mortality. A retrospective analysis of prospectively collected data of patients with the PIVSR admitted to our center from November 2004 to February 2012 was performed. Variables were analyzed using two-dimensional correspondence analysis. There were 25 patients (12 males and 13 females) with mean age 70.2 years (47-82) operated on; 17 (68%) presented with anterior and 8 (32%) with posterior PIVSR. Eighteen patients (72%) had acute heart failure, 13 (52%) presented with cardiogenic shock. Before surgery, intraaortic balloon pump (IABP) had 20 (80%) patients; in 4 (16%) a ventricular assist device was used, either Extracorporeal Membrane Oxygenation (ECMO) or centrifugal pumps as biventricular assist. Operative mortality was 40% (10 pts.). Four patients (12%) had small non-significant recurrent shunt on postoperative echocardiography. Although majority of patients with PIVSR have significant heart failure prior to surgery the operative mortality remains comparable to older studies. Predictors of perioperative death were concomitant surgical reconstruction of the left ventricle, renal impairment before operation, male gender, history of coronary artery disease, PIVSR location posterior, and shock at surgery.
Keywords: ruptura komorového septa; lidé středního věku; lidé; senioři nad 80 let; senioři; mužské pohlaví; kardiochirurgické výkony; retrospektivní studie; Female; Male; Ventricular Septal Rupture; Aged; Retrospective Studies; Cardiac Surgical Procedures; Middle Aged; Aged, 80 and over; ženské pohlaví; Humans